Some Studies on the Effect of Annona muricata and Cisplatin on Rats Suffering from Liver Cancer - Zein , Nabila; Yassin, Fathy; Hassan, Amira (Journal of Advanced Veterinary Research, 2023)
This study aimed to evaluate the effect of Carbone tetrachloride (CCl4) on inducing liver cancer beside the effect of Cisplatin and Annona muricata on the treatment of liver cancer in rats and to investigate the efficacy, safety and tolerability of Annona muricata leaf. A total of 56 healthy male-albino rats (3-4 months old), weighing between 180-200 g 9Average body weight) were divided into two main groups. Group (1) contained 14 healthy rats left without any treatment (Negative control), then 42 healthy rats received IP injection with CCl4 at dose of 1 ml/ kg/ twice every week for 8 weeks to develop Hepatocellular carcinoma (HCC), after the onset of liver cancer, rats were separated into three equal groups (14 in each) as follow: Group (2) included 14 rats suffered from liver cancer and left without any treatment (Positive control). Group (3) involved 14 rats suffered from liver cancer and received IP injection of Cisplatin at dose of 6 mg/kg/week for 4 weeks. Group (4) included 14 rats that had liver and received Annona muricata orally at dose of 300 mg/kg every day for 4 weeks. At the end of experiment blood samples were taken from all rats in all groups to preserve the serum for estimation of serum liver enzymes (Aspartate aminotransferase (AST), Alanine aminotransferase (ALT) and Alkaline phosphatase (ALP)), Nuclear factor (erythroid-derived 2)-like 2 (Nrf2), B-cell lymphoma 2 (BCL2), Transforming growth factor beta (TGF-Î²) and nuclear factor kappa-light-chain-enhancer of activated B cells (NFÎºB). Liver tissue was collected for gene expression determination of Caspase-3 and Caspase-9 levels, and Immunohistochemistry studies carried out to measure Silver-stained Nucleolar organizer regions (AgNORs) and alpha smooth muscle actin (Î±-SMA). In the current work, it has been found that; rats with HCC showed significant increase in ALT, AST, ALP, Nrf2, BCL2, TGF-Î², NFÎºB, Caspase-3 and Caspase-9 levels in comparison with negative control rats. Rats with HCC treated with Cisplatin displayed non-significant decrease in serum AST, ALT, ALP and Nrf2 beside significant decrease in BCL2, TGF-Î², NFÎºB, Caspase-3 and Caspase-9 in comparison with positive control rats. Rats with HCC treated with Annona muricata displayed significant decrease in AST, ALT, ALP, Nrf2, BCL2, TGF-Î², NFÎºB, Caspase-3 and Caspase-9 in comparison with positive control rats. Photomicrograph of peroxidase stained rat liver of negative control group showing negative expression for AgNORs beside negative expression for Î±-SMA. Photomicrograph of peroxidase stained liver of rats with HCC showed positive severe expression for AgNORs beside moderate to severe positive expression for Î±-SMA. Photomicrograph of peroxidase stained liver of rats with HCC treated with Cisplatin showed positive mild to moderate expression neither for AgNORs beside mild to moderate positive expression for Î±-SMA. Photomicrograph of peroxidase stained liver of rats with HCC treated with Annona muricata showed positive mild expression for AgNORs beside negative to mild positive expression for Î±-SMA. In conclusion, the present study indicates that Annona muricata gives significant improvements in treatment of Albino rats with liver cancer, due to its antioxidant, anti-inflammatory and anticancer effects beside improvements of hepatorenal cellular carcinoma.